Sistem Pakar Diagnosa Penyakit Kulit di Bagian Wajah dengan Metode Bayesian Probability dan Gray Level Co-Occurrence dan Color Coherence Vector - Atmodjo, Willy Wrekso (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
This expert system uses the Bayesian Probability method for diagnosis with experts and GLCM and CCV methods for diagnosis with photo imagery. With the Bayesian method the user should choose the symptomsl, while for the image method the user is expected to input the image to be used. Expert system is created by using visual studio program with Visual Basic programming language. This expert system is used for users can diagnose the onset of facial skin diseases experienced. Testing is done by blackbox testing method. The test results showed that expert system with Bayesian Probability method and GLCM and CCV image method showed good and accurate result